A Multilocus Sequence Analysis Scheme for Phylogeny of Thioclava Bacteria and Proposal of Two Novel Species - Yang Liu; Yang Liu; Qiliang Lai; Zongze Shao; Zongze Shao (Frontiers in Microbiology, 2017)
A multilocus sequence analysis (MLSA) was established and performed on the genus Thioclava, including 23 strains isolated from diverse marine environments, with the aim of better differentiation of strains and species within this genus. The study was based on sequences of 16S rRNA gene and five protein-coding housekeeping genes, gyrB, rpoD, dnaK, trpB, and recA. In contrast to 16S rRNA gene-based tree that was unable to separate some species within this genus, each tree based on a single housekeeping gene and MLSA had consistently defined seven clades, corresponding to the five established ones and two novel ones. The digital DNA-DNA hybridization and average nucleotide identity analyses based on genome sequences of the representative strains reconfirmed the validity of the MLSA analysis, and recommended a 97.3% MLSA similarity as the soft species threshold and nine species representing the five known and four putative novel species. Two of the four new species were identified as Thioclava sediminum sp. nov. (type strain TAW-CT134T = MCCC 1A10143T = LMG 29615T) and Thioclava marinus sp. nov. (type strain 11.10-0-13T = MCCC 1A03502T = LMG 29618T) by using a polyphasic taxonomic approach. Taken together, the newly established MLSA in this study first described the variability and phylogeny of the genus Thioclava which contributes to better understanding its ecology and evolution.